Legal Harmonization in the Era of the New Indonesian Penal Code: A Study on the Application of Restorative Justice in Traffic Accidents - Djajadi Djajadi; Dudung Hidayat; Sri Primawati Indraswari (Ann Publisher, 2026)
Background. This study is grounded in the shifting paradigm of punishment within the New Indonesian Penal Code, which emphasizes a restorative justice approach, amidst the continued dominance of a formalistic framework under the Traffic and Road Transportation Law, particularly in cases of negligence resulting in death. Aims. The study aims to analyze the differences in legal regulation and the implications of applying restorative justice within these two legal regimes. Methods. The research employs a qualitative approach using normative legal research methods, relying on document analysis of statutory regulations, legal principles, sentencing principles, and the new paradigm introduced by the Indonesian Penal Code. Result. The findings reveal a normative inconsistency between the Traffic Law, which restricts restorative justice based on the severity of criminal sanctions, and the New Penal Code, which allows for restorative approaches based on the nature of the offense and specific circumstances, including reconciliation and compensation. Conclusion. It is concluded that the formalistic approach in law enforcement practices has not yet fully aligned with the restorative direction of contemporary penal reform. Implementation. The study highlights the need for regulatory harmonization and adaptive law enforcement policies that are more responsive to the principles of substantive justice and modern penal paradigms.